Toward a Design of Blood Donation Management by Blockchain Technologies - Quynh, Nga Tang Thi; Son, Ha Xuan; Le, Trieu Hai; Huy, Hung Nguyen Duc; Vo, Khanh Hong; Luong, Huong Hoang; Tuan, Khoi Nguyen Huynh; Anh, Tuan Dao; Nguyen, The Anh; Duong-Trung, Nghia (Computational Science and Its Applications - ICCSA 2021, 2021)
Nowadays, due to rapid changes in the population structure, which results in lower fertility rates and rapid aging, the demand for blood supply is increasing a lot. In most countries, blood quality and origin are managed by blood management information systems, such as national institutions. However, the existing system lacks limitations in that it lacked detailed blood information, which causes difficulties in managing blood quality, supply, and demand. Therefore, to solve this problem, this paper proposes an innovative system that supports managing the blood information, providing more detailed blood information such as blood consumption and disposal. A blockchain is currently a standard tool implemented in research, especially in supply chain management such as the medical field or financial system. Notably, private blockchain techniques with limited participants are relatively fast and reliable, making them suitable for B2B (Business-to-Business) transactions. Therefore, the proposed system is based on the architecture of Hyperledger Fabric. Moreover, the recorded information in blockchain technology will support dealing with the supply and demand of blood in the national institutions so that it is easier for national institutions to solve emergencies.